Emotional intelligence and self-esteem: Personal competencies necessary for physicians - Molero Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Martos Martínez, África; Gázquez Linares, José Jesús (Frontiers in Medicine, 2022)
INTRODUCTION. Even though emotional intelligence and self-esteem are truly important variables in healthcare, the fact is that there are few studies on these constructs in Spanish physicians. The objective was to analyze the relationship between self-esteem and emotional intelligence in Spanish physicians, and their relationship with sociodemographic and employment variables. METHODS. The study included a sample of 180 physicians with a mean age of 34.61, 76.7% of whom were women. The physician completed the Rosenberg self-esteem scale, the Brief Emotional Intelligence Inventory for Senior Citizens and a questionnaire on sociodemographic and work characteristics through a CAWI (Computer Assisted Web Interviewing). RESULTS. The results showed that the interpersonal factor of emotional intelligence diminished with age and number of children. Furthermore, women scored significantly higher in interpersonal emotional intelligence and men in adaptability. Physicians with stable contracts (46.1%) scored higher in all the emotional intelligence variables, with almost a small effect size. In the relationship between self-esteem and emotional intelligence, it was found that global self-esteem of physicians was positively related to the Stress Management, Adaptability and Mood dimensions. Physicians with high self-esteem (72.8%) showed better Stress Management and Mood than those with low self-esteem (6.1%), while in the Adaptability factor, physicians with high global self-esteem scored higher than those with medium levels (21.1%). CONCLUSION. The need for a stable employment strategy was demonstrated, since this has repercussions on personal competencies of physicians as well as training in developing those consequences, since they improve physicians’ quality of care and leadership, especially women with temporary contracts or with medium or low self-esteem.